PENGARUH BIAYA PELAYANAN TERHADAP PENJUALAN WIFI INDIHOME PADA PLASA TELKOM RAJAWALI (PERIODE 2017 - 2020) - Upayarto, Budi; Solehudin, Solehudin (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2023)
The study aims to determine: (1) Service Fees, (2) Sales, and (3) The influence of Service Fees on Sales at Plaza Telkom Rajawali for the 2017-2020 period. Data collection techniques were carried out through observation, interviews, documentation and literature studies. The type of data used is quantitative data in the form of Service Fees and Sales for the 2017–2020 period. The data collected was then analyzed using Simple Linear Regression Analysis with the SPSS Version 22 tool. The research results show that, (1) Service and Sales Fees increase every year and experience a significant decrease in June–July each 2017–2020, (2) Service Fees have a significant influence on sales with a regression coefficient for the service fees variable of 2.357. The strong relationship between the two research variables is shown by the correlation coefficient r = 0.940, with a determination coefficient of 88.36%, which means that 11.64% of sales are influenced by other variables. Significance is shown based on the results of a comparison between tcount values ​​that is greater than ttable, namely (18.748 > 2.01290).